Disclosure of information Norwich pharmacal and related principles - Bushell, Simon; Bushell, Simon; Milner-Moore, Gary (London : Bloomsbury Professional, 2022)
Disclosure of Information: Norwich Pharmacal and Related Principles offers clear and concise procedural guidance and comprehensive legal analysis of the key ingredients of the jurisdiction. It is the only book available that deals solely with this important and distinctive power of disclosure developed (and continuing to develop) in the English Courts. The book combines detailed legal commentary with sound practical guidance and is essential reading for litigation practitioners and practitioners involved in commercial disputes..
Chapter 1: Introduction --Chapter 2: Overview --Chapter 3: Background to the Norwich Pharmacal case --Chapter 4: The Norwich Pharmacal case --Chapter 5: Full Information to Assist the Victim of Fraud: Banker's Trust --Chapter 6: Extending Norwich Pharmacal --Chapter 7: Wongdoing --Chapter 8: Involvement --Chapter 9: Necessity --Chapter 10: Discretion and Scope of Relief --Chapter 11: Common Objections --Chapter 12: Proecedural Considerations --Chapter 13: Modern applications --Chapter 14: Extra-territorial Scope -Chapter 15: Related Jurisdictions --Chapter 16: International Arbitration --Chapter 17: Where Next for Norwich Pharmacal? --Appendix: Sample Orders --A: Simple Norwich Pharmacal Order in respect of an Identity --B: Bankers Trust Order.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Civil procedure -- Litigation -- United Kingdom; Fraud -- United Kingdom; Law; Disclosure of information -- Law and legislation; Criminal investigation -- Law and legislation; Copyright; Great Britain